2020
DOI: 10.3389/fnut.2020.612875
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gut Microbiota and Oxidative Status by β-Carotene in Late Pregnant Sows

Abstract: Recent evidences suggest that gut microbiota plays an important role in regulating physiological and metabolic activities of pregnant sows, and β-carotene has a potentially positive effect on reproduction, but the impact of β-carotene on gut microbiota in pregnant sows remains unknown. This study aimed to explore the effect and mechanisms of β-carotene on the reproductive performance of sows from the aspect of gut microbiota. A total of 48 hybrid pregnant sows (Landrace × Yorkshire) with similar parity were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Multiple studies have focused on the effect of β-carotene on offspring, however, the impact of β-carotene on maternal and postpartum recovery is not clear. Our recent study has shown that dietary supplementation of β-carotene had a positive effect on the reproductive performance of sows ( 8 ), and in vitro inhibitory effect of β-carotene on cytokines was revealed by Lin et al. ( 25 ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Multiple studies have focused on the effect of β-carotene on offspring, however, the impact of β-carotene on maternal and postpartum recovery is not clear. Our recent study has shown that dietary supplementation of β-carotene had a positive effect on the reproductive performance of sows ( 8 ), and in vitro inhibitory effect of β-carotene on cytokines was revealed by Lin et al. ( 25 ).…”
Section: Discussionmentioning
confidence: 97%
“…Gut microbiota was characterized by 16S rRNA gene sequencing as described previously ( 8 ). Briefly, Total DNA was extracted from cecum contents by using a DNA Isolation Kit (MoBio Laboratories, Carlsbad, CA, USA) following the manufacturer’ s manual.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggested that the β-carotene lower the composition of Firmicutes such as Lachnospiraceae AC2044 group, Lachnospiraceae NK4B4 group, as well as Ruminococcaceae UCG-008, but on the other hand significantly enriched the Proteobacteria and Actinobacteria having related to NO synthesis. It was concluded that the supplementation of dietary β-carotene might rise antioxidant enzyme activity and NO which is an important to promote the neonatal blood circulation, through regulating gut microbiota in sows [169].…”
Section: Fat-soluble Vitaminsmentioning
confidence: 99%